Factors Associated with Nursing Documentation in Electronic Medical Records at RSUD Sawerigading Palopo, 2025 - Bahar, Pratiwi; Sastria, Andi; Asriadi (AACENDIKIA: Journal of Nursing, 2025)
Nursing documentation in electronic medical records (EMRs) is a critical component in enhancing the efficiency of nursing services and the quality of patient care. However, the implementation of EMRs in some hospitals still faces various challenges. Factors such as nurses’ knowledge, performance, and supervision are believed to influence the quality of nursing documentation. This study aimed to analyze the factors associated with nursing documentation in EMRs at RSUD Sawerigading Palopo. A quantitative study with a cross-sectional approach was conducted involving 40 nurses working in inpatient wards, selected through purposive sampling. The results showed that knowledge, performance, and supervision were significantly associated with the quality of nursing documentation in EMRs. These findings suggest that improving training and supervision for nurses may enhance the quality of nursing documentation in electronic medical records.